Acceptance commitment therapy (ACT) for psychological distress associated with inflammatory bowel disease (IBD): protocol for a feasibility trial of the ACTforIBD programme. Issue 6 (10th June 2022) - Evans, Subhadra; Olive, Lisa; Dober, Madeleine; Knowles, Simon; Fuller-Tyszkiewicz, Matthew; O, Eric; Gibson, Peter; Raven, Leanne; Gearry, Richard; McCombie, Andrew; van Niekerk, Leesa; Chesterman, Susan; et al.
Abstract : Introduction: Inflammatory bowel disease (IBD) involves an abnormal immune response to healthy gut bacteria. When a person develops IBD, their susceptibility to anxiety and/or depression increases. The ACTforIBD programme, specifically designed for people with IBD and comorbid psychological distress, draws on acceptance and commitment therapy (ACT), which promotes acceptance of situations that cannot be solved such as persistent physical symptoms. There are no ACT trials for IBD using an active control group or a telemedicine approach, which is important to improve accessibility, particularly in the context of the ongoing COVID-19 pandemic. The ACTforIBD programme is administered online with a 4-hour therapist involvement per participant only; if successful it can be widely implemented to improve the well-being of many individuals with IBD. Methods and analysis: Our team have codesigned with consumers the ACTforIBD programme, an 8-week intervention of 1-hour sessions, with the first three sessions and the last session delivered one-to-one by a psychologist, and the other sessions self-directed online. This study aims to evaluate the feasibility and preliminary efficacy of ACTforIBD to reduce psychological distress in patients with IBD. Using a randomised controlled trial, 25 participants will be randomised to ACTforIBD, and 25 patients to an active control condition. Ethics and dissemination: This protocol has been approved by Deakin University Research Ethics Committee in September 2021 (Ref. 2021-263) and the New Zealand Central Health and Disability Ethics Committee in December 2021 (Ref. 2021 EXP 11384). The results of this research will be published in peer-reviewed journals and shared with various stakeholders, including community members, policy-makers and researchers, through local and international conferences. Trial registration number: ACTRN12621001316897.